Contro l’egemonia di genere: Il voguing come danza di resistenza - Zardi, Andrea (Mimesis Journal, 2020)
Dance is rooted in the ritual sphere of a specific time and it interact with the political sphere, questioning ideological and social practices and pursuing strategies of resistance against them. The dancing body, first, relies on a system of conventions that defines itself in every society and it carries out an ideological power. Around this theory, this essay examines the phenomenon of Voguing, highlighting the redefinition of gender identities, ritual practices and the function of community. Through the historical analysis of ballroom culture phenomenon, a multiform practice of collective identity is outlined and it responds to urgent social phenomena. Performance Studies, Gender Studies and the analysis of media products – carried out in the last decades – could help us to understand how sub-cultural community processes have become part of a pop performativity.